Learning Actions and Action Verbs from Human-Agent Interaction - Mohan, Shiwali (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
The goal of my research is to design agents that learn from human-agent interaction. Specifically, I am interested in acquisition of procedural, conceptual and linguistic knowledge related to novel actions from human-agent collaborative task execution.